K27-linked RORγt ubiquitination by Nedd4 potentiates Th17-mediated autoimmunity - Qiuming Zeng; Hui Guo; Na Tang; Pranav S. Renavikar; Nitin J. Karandikar; Amy E. Lovett-Racke; Michael K. Racke; Chengkai Yan; Rong Tang; Sushmita Sinha; Krishnendu Ghosh; Jeremy P. Ryal; et al. (Journal of Biomedical Science)
Abstract Background The HECT E3 ubiquitin ligase Nedd4 has been shown to positively regulate T cell responses, but its role in T helper (Th) cell differentiation and autoimmunity is unknown. Th17 cells are believed to play a pivotal role in the development and pathogenesis of autoimmune diseases. Nevertheless, the regulation of RORγt activation during Th17 cell differentiation by TCR signaling is yet to be elucidated. These uncharted aspects inspire us to explore the potential role of Nedd4 in Th17-mediated autoimmunity. Methods We evaluated the impact of Nedd4 deficiency on mouse T cell development and differentiation using flow cytometry and siRNA transfection, and subsequently validated these findings in T cells from patients with multiple sclerosis (MS). Furthermore, we investigated the influence of Nedd4 deficiency on Th17-mediated autoimmunity through experimental autoimmune encephalomyelitis (EAE), a mouse model of MS. Subsequently, we elucidated the molecular mechanism underlying the interaction between Nedd4 and RORgt through immunoprecipitation, mass spectrometry analysis, and lentiviral transduction. Additionally, we identified Nedd4 as an E3 ubiquitin ligase for RORγt. Moreover, we characterized the tyrosine residue sites and polyubiquitination patterns involved in RORγt ubiquitination. Results In this study, we report that loss of Nedd4 in T cells specifically impairs pathogenic and non-pathogenic Th17 responses, and Th17-mediated EAE development. At the molecular level, Nedd4 binds to the PPLY motif within the ligand binding domain of RORγt, and targets RORγt at K112 for K27-linked polyubiquitination, thus augmenting its activity. Conclusion Nedd4 is a crucial E3 ubiquitin ligase for RORγt in the regulating Th17 cell development and offers potential therapeutic benefits for treating Th17-mediated autoimmune diseases.